A simple graphene modified electrode for the determination of antimony(III) in edible plants and beverage. (15th January 2022) - Liendo, Fabiana; de la Vega, Amaya Paz; Jesus Aguirre, Maria; Godoy, Fernando; Martí, Angel A.; Flores, Erick; Pizarro, Jaime; Segura, Rodrigo
Highlights: GC/rGO was applied for the determination of Sb(III) in food samples. rGO improves preconcentration and sensitivity for Sb(III) determination. The analytical validation of GC/rGO shows satisfactory results with RSD < 10%. The lineal range for Sb(III) was 10–60 µg L −1 with a detection limit of 2.5 µg L −1 . Abstract: Antimony(III) is a rare electroactive specie present on Earth, whose concentration is not typically determined. The presence of high concentrations of antimony is responsible for a variety of diseases, which makes it desirable to find convenient and reliable methods for its determination. We have developed a convenient glassy carbon modified electrode with electroreduced graphene oxide GC/rGO for the first time determination of Sb(III) in commercial lettuce, celery, and beverages. The surface of the electrode was characterized by scanning electron microscopy (SEM) and cyclic voltammetry, indicating a heterogeneous and rough surface with a real area of 0.28 cm 2, which is 2.5 times the area of GC. The optimal chemical and electrochemical parameters used were: sodium acetate buffer (pH = 4.3), an accumulation potential of −1.0 V and an accumulation time of 150 s. The analytical validation was developed evaluating the linear range (10–60 µg L −1 ), limit of detection (2.5 µg L −1 ), accuracy, repetibility and reproducibility with satisfactory results (relative standard deviation (RSD) values lower than 10%). All the analyzes performed in real samples by stripping voltammetry were compared with GF-AAS, showing statistically similar values, demonstrating that GC/rGO could be effectively applied in the analysis of food samples.